OPTIMIZATION OF DOMESTIC CARGO DELIVERY HANDLING TO IMPROVE SERVICESAT CARGO TERMINALS - Zidane Al Akbar, Mukhammad; Fatimah, Siti; Olieve, Arnaz (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The cargo terminal is one of the services inside the airport to process shipments and receipts of air, domestic and international cargo. The purpose of this study is to describe the conditions of laying cargo shipping equipment, and find out the handling of cargo by cargo delivery officers at the Cargo Terminal of Sultan Aji Muhammad Sulaiman Sepinggan International Airport Balikpapan. This study uses a type of qualitative descriptive research to determine the handling of domestic cargo at the cargo terminal and the laying conditions at the cargo delivery facility have been optimized and in accordance with applicable regulations. With data collection methods in the form of observation, interviews, and documentation of research objects. The results of the study found baggage cart facilities that were not in accordance with their placement, and the handling of goods by cargo terminal officers that were not in accordance with standard operating procedures. So that conclusions can be drawn by returning the placement and handling of cargo goods according to the rules and the use of empty areas in storage as a step to minimize the level of congestion in the staging area at the Cargo Terminal of Sultan Aji Muhammad Sulaiman Sepinggan International Airport Balikpapan.